2015
DOI: 10.3233/jad-141937
|View full text |Cite
|
Sign up to set email alerts
|

Atlas-Based Diffusion Tensor Imaging Correlates of Executive Function

Abstract: Impairment in executive function (EF) is commonly found in Alzheimer’s Dementia (AD) and Mild Cognitive Impairment (MCI). Atlas-based Diffusion Tensor Imaging (DTI) methods may be useful in relating regional integrity to EF measures in MCI and AD. 66 participants (25 NC, 22 MCI, and 19 AD) received DTI scans and clinical evaluation. DTI scans were applied to a pre-segmented atlas and fractional anisotropy (FA) and mean diffusivity (MD) were calculated. ANOVA was used to assess group differences in frontal, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
5
11
0
Order By: Relevance
“…Decreased FA in a number of tracts has been shown to be a marker of AD dementia, relating changes in diffusive properties of white matter to impairment in AD dementia [20]. FA has been shown to be less sensitive to the early changes of mild cognitive impairment [21]; however, the significant differences that we found in FA between those with high and executive abilities suggests that FA changes in MCI may be related to executive deficits [22]. Our study confirms that the white matter changes found previously in AD may manifest earlier as a function of diminished executive abilities in MCI, and that these diminished abilities are likely to accompany early white matter changes in specific white matter tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased FA in a number of tracts has been shown to be a marker of AD dementia, relating changes in diffusive properties of white matter to impairment in AD dementia [20]. FA has been shown to be less sensitive to the early changes of mild cognitive impairment [21]; however, the significant differences that we found in FA between those with high and executive abilities suggests that FA changes in MCI may be related to executive deficits [22]. Our study confirms that the white matter changes found previously in AD may manifest earlier as a function of diminished executive abilities in MCI, and that these diminished abilities are likely to accompany early white matter changes in specific white matter tracts.…”
Section: Discussionmentioning
confidence: 99%
“…The unique aspect of this approach is an implementation DTI atlas with fine delineation of DTI-visible white matter structures. If it is hypothesized the white matter pathology of AD is tract-specific, tract-based voxel grouping, such as Tract-Based Spatial Statistics (TBSS), can be applied (Nowrangi et al, 2015; Smith et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Currently, a great deal of attention is being paid to the study of EF and their relationship with the white matter, and the cortico-cortical brain networks, altered during the neurodegenerative process of Alzheimer’s disease [ 48 ]. Using advanced imaging techniques such as diffusion tensor, it has been confirmed the involvement of frontal and posterior brain areas (parietal lobes) in patients with MCI and impaired EF [ 49 ]. In addition to cingular alterations [ 50 ].…”
Section: Discussionmentioning
confidence: 99%